Quintana: Ferramenta de Avaliação de Redações - Soares, Vanessa; Freire, Danilo; Bittencourt, Lucas; Feitosa, Alexander; Pavão, Jorge; Carvalho, Flavio; Belloze, Kele; Guedes, Gustavo; Bezerra, Eduardo (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
This article presents Quintana, an AI-based essay assessment tool for Portuguese-language argumentative texts, based on the competencies of the Exame Nacional do Ensino Médio (ENEM). The tool uses machine learning models trained on essays extracted from the “Brasil Escola” platform and allows students to submit essays and receive predicted scores for each competency. The results are presented in a pedagogically organized way, with scores and feedback grouped by competency, supporting formative use by students and teachers without replacing teacher assessment. This demo showcases how modern Natural Language Processing techniques can be integrated into a practical and accessible educational solution with meaningful social impact.